The Effect of Acupressure on Dysmenorhore in Adolescent Women Year 2022 - Mardianti, Lina; Skania, Pratiwi Cahya; Sari, Nina Yuliana; Rohmah, Hajar Nur Fathur; Safitri, Resti; Rezaldi, Firman (Jurnal Biologi Tropis, 2024)
Dysmenorrhea is a problem that women often experience every month and is accompanied by menstrual pain. If dysmenorrhea is not evaluated and treated, it will result in a decrease in academic achievement of 51.4%, limited activity during menstruation 40.9%, absenteeism from class 31.1%, decreased concentration 43.3%, decreased appetite and changes in sleep patterns 42. 7% and withdrawal from the community or relationships 63%. This study aims to determine the effect of acupressure therapy on dysmenorrhea in adolescents. The research method is Quasi Experimental with a group pre-post test design. Data were analyzed univariately and bivariately. The results of the study found a description of the level of dysmenorrhoea pain experienced by respondents before and after acupressure, showing that after acupressure the majority of respondents only felt mild pain (scale 1-3), namely 61.2% of respondents and the rest no longer felt pain (scale 0), namely as many as 35.8% of respondents.